Exchange-rate policies for emerging market economies - Sweeney, Richard J. (Richard James), 1944-; Wihlborg, Clas; Willett, Thomas D. (Political economy of global interdependence., 2019)
With the loss of Soviet control in Central and Eastern Europe, as well as the move toward economic liberalization in many developing countries, a huge increase in the number of convertible currencies in the world has occurred.